New Atypophthalmus (Diptera: Limoniidae) from South Korea - Podenas, Sigitas; Podeniene, Virginija; Seo, Hong-Yul; Kim, A-Young; Park, Sun-Jae; Byun, Hye-Woo; Kim, Heung-Chul; Aukštikalnienė, Rasa (Zootaxa, 2020)
Two new species of crane flies belonging to the genus Atypophthalmus Brunetti, 1911, A. (Atypophthalmus) kleini Podenas, sp. nov. and A. (Microlimonia) jeju Podenas & Podeniene, sp. nov. collected in South Korea in 2017 and 2019 are described and illustrated. Larvae and female pupa for A. (Microlimonia) jeju sp. nov. are described. The pupa for the subgenus A. (Microlimonia) is described for the first time. An updated list and key for adults of all Korean Atypophthalmus are presented.